Inventarisasi Spasial Infrastruktur Jaringan Listrik untuk Optimalisasi Pelayanan Kelistrikan di Musi Rawas - Achmad Asril Asri; Oknovia Susanti (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Electricity service quality depends not only on physical network expansion but also on the availability of accurate, traceable, and spatially integrated asset data. This study aims to formulate an infrastructure inventory plan for electricity distribution networks as a basis for optimizing electricity services in Musi Rawas Regency, Indonesia. A descriptive-technical approach was applied using administrative maps, spatial planning documents, distribution network maps, feeder single-line diagrams, January 2026 customer data, bill of quantity documents for electricity and public street lighting, and the planned network drawing for Mandi Aur Village. The results show that 14 target districts served approximately 101,932 customers, consisting of 78,564 postpaid and 23,368 prepaid customers. Tugumulyo, Megang Sakti, Muara Kelingi, and Muara Lakitan represented the largest customer concentrations and should be prioritized for detailed asset verification. The proposed inventory object includes medium-voltage lines, low-voltage lines, poles, distribution transformers, protection equipment, public street lighting, panels, and operation-worthiness documents. The inventory database should include unique asset codes, coordinates, feeder identity, specifications, physical condition, photographs, operational status, and follow-up actions. Spatial inventory is expected to improve maintenance planning, outage response, public lighting management, safety control, and evidence-based network development.